2022
DOI: 10.1007/s11920-022-01360-1
|View full text |Cite
|
Sign up to set email alerts
|

E-Mental Health for People with Personality Disorders: A Systematic Review

Abstract: Purpose of Review Provision of mental health services through digital technologies (e-mental health) can potentially expand access to treatments for personality disorders (PDs). We evaluated studies on e-mental health for PDs published over the last 3 years (2019–2022). Recent Findings Studies published in English that used e-mental health to treat people with PDs or PD-related symptoms were identified. We identified 19 studies, including four randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Nonetheless, these findings align with previous reviews on digital interventions in BPD , personality disorders (Xie et al, 2022), and in other clinical populations (Lattie et al, 20219;Sin et al, 2020;Stefanopoulou et al, 2020) which have found positive secondary outcomes such as effects on well-being, positive service user feedback and high acceptance of digital mental health interventions. However, these results also speak against findings from Ilagan et al (2020) previous review on mHealth intervention that did not identify an effect on general psychopathology/psychological distress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, these findings align with previous reviews on digital interventions in BPD , personality disorders (Xie et al, 2022), and in other clinical populations (Lattie et al, 20219;Sin et al, 2020;Stefanopoulou et al, 2020) which have found positive secondary outcomes such as effects on well-being, positive service user feedback and high acceptance of digital mental health interventions. However, these results also speak against findings from Ilagan et al (2020) previous review on mHealth intervention that did not identify an effect on general psychopathology/psychological distress.…”
Section: Discussionsupporting
confidence: 90%
“…This is not dissimilar to findings from Ilagan et al (2020)'s systematic reviews on digital interventions for BPD which reported no or very small differences in outcomes between control and digital intervention groups and which included many studies with active control groups. Similarly, reviews which have focused on digital interventions for personality disorders digital often have been more cautious to interpret results on the efficacy of digital interventions for personality disorders (Xie et al, 2022) due to the limited number of large‐scale RCTs with active‐control groups that have been conducted to date. Equally, reviews looking at other mental health difficulties often find positive effects for digital interventions only when comparing these to inactive control groups (Goldberg et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to indicate increased digitization, which reflects the society we find ourselves in and how this society also affects the homeless situation population. Notwithstanding, the number of studies that have employed such devices is still small and less recent compared to other populations, such as people with depressive disorders [ 55 , 56 , 57 ], adolescents [ 58 , 59 ], and people with personality disorders [ 60 , 61 ], among others. This, once again, seems to indicate that the homeless context population represents a forgotten gap in the research field and, consequently, in the clinical and political domain.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) , there is simply not enough evidence to conclude that mHealth actually leads to the expected benefits. Empirical literature provides numerous examples of devices that fail to capture reliable metrics even when it comes to simple parameters such as daily step counts ( Crawford et al ., 2015 ) or heart rate ( Lomborg et al , 2020 ), and this is even more problematic when mHealth devices are used to monitor more complex factors such as mental health ( Xie et al ., 2022 ). Moreover, the authors note that many devices tend to break down, interrupting the continuity of monitoring or erasing the users’ data in the process ( Klugman et al ., 2018 ; Kristensen et al ., 2021 ).…”
Section: Healthism As a Threat To The Promises Of Mobile Health Techn...mentioning
confidence: 99%